Baseline EEG Pattern on Continuous ICU EEG Monitoring and Incidence of Seizures. Issue 2 (April 2015) - Swisher, Christa B.; Shah, Dharmen; Sinha, Saurabh R.; Husain, Aatif M.
Abstract : Purpose: To identify the probability of detecting nonconvulsive seizures based on the initial pattern seen in the first 30 minutes of continuous EEG (cEEG) monitoring. Methods: Continuous EEG monitoring reports from 243 adult patients were reviewed, assessing the baseline cEEG monitoring pattern and the presence of seizures during the entire monitoring period. The baseline EEG patterns were classified into nine categories: seizures, lateralized periodic discharges, generalized periodic discharges, focal epileptiform discharges, burst suppression, asymmetric background, generalized slowing, generalized periodic discharges with triphasic morphology, and normal. Results: Overall, 51 patients (21%) had nonconvulsive seizures at any time during cEEG monitoring. Notably, 112 patients had generalized slowing as the initial EEG pattern, and none of these patients were noted to have seizures. Seizure rates among the types of baseline EEG findings were as follows: lateralized periodic discharges (56%, n = 9), burst suppression (50%, n = 10), generalized periodic discharges (50%, n = 2), normal (33%, n = 3), focal epileptiform discharges (31%, n = 35), and asymmetric background (11%, n = 46). Conclusions: Patients with only generalized slowing seen on the baseline EEG recording are unlikely to develop seizures on subsequent cEEG monitoring. Depending on the clinical circumstance, the standard duration of cEEG recording (24–48 hours) may be unnecessary in patients with generalized slowing as their only cEEG abnormality.